Polydopamine‐Assisted Electroless Deposition of Magnetic Functional Coatings for 3D‐Printed Microrobots - Shuo Zhang; Caroline F. Harms; Zenghao Zhang; Jiwon Lim; John T. Heron; Jinsang Kim; Abdon Pena‐Francesch (Advanced Intelligent Systems)
Magnetic microrobots are attractive tools for operation in confined spaces due to their small size and untethered wireless operation, particularly in biomedical and environmental applications. Over years of development, many microrobot fabrication methods have been developed; however, they typically require costly specialized physical vapor deposition (PVD) vacuum instrumentation and present homogeneity and conformality coating problems (especially in complex 3D structures). Herein, a solution‐based polydopamine (PDA)‐assisted electroless deposition method is developed to deposit a superparamagnetic nickel thin film on microrobots. The multilayered functional film design comprises PDA as an adhesive primer and reducing agent, silver nanoclusters as catalysts, and a nickel magnetic top film, all deposited in a batch solution‐based process on glass and 3D‐printed polymer substrates. This multilayer magnetic coating is implemented and demonstrated in three magnetic microrobot archetypes, including arbitrarily‐shaped active particles, microrollers, and helical swimming microrobots, each using distinct actuation working mechanisms. Due to the material‐independent interfacial adhesive properties of PDA, this multilayer functionalization strategy can open up new magnetic microrobot fabrication schemes with a broad compatibility with materials and structures (including complex 3D‐printed polymer microstructures) and without the need for and limitations of PVD coating approaches.